2005
DOI: 10.1097/01.brs.0000181053.38677.c2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Interbody Cage Positioning on Lumbosacral Vertebral Endplate Failure in Compression

Abstract: The placement of 2 small interbody cages posterolaterally tended to result in higher failure loads than central cage placement, although the results were not statistically significant. It is noteworthy that cage placement in any position resulted in a less stiff construct in compression than with an intact disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 18 publications
4
24
1
Order By: Relevance
“…The strongest region is located postero-laterally, just in front of the pedicles, with more than twice the strength of the central endplate. In addition, another biomechanical study demonstrated that a dorso-lateral placement of interbody cages in combination with a pedicle screw system results in a 20% higher failure loads than a central cage placement, although the results were not statistically significant [17]. Thus, under in vitro settings, a cage placement in the dorsolateral regions seems to have the advantage of minimizing subsidence when compared to a central or ventral cage placement.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The strongest region is located postero-laterally, just in front of the pedicles, with more than twice the strength of the central endplate. In addition, another biomechanical study demonstrated that a dorso-lateral placement of interbody cages in combination with a pedicle screw system results in a 20% higher failure loads than a central cage placement, although the results were not statistically significant [17]. Thus, under in vitro settings, a cage placement in the dorsolateral regions seems to have the advantage of minimizing subsidence when compared to a central or ventral cage placement.…”
Section: Discussionmentioning
confidence: 94%
“…To prevent cage migration, the interface between the implant and the vertebral bone must have sufficient strength to resist the large in vivo loading. Biomechanical studies have shown that the strength of this interface varies across the surface of the endplate [11,17]. Anatomical studies have shown that the density and thickness of the vertebral endplate increase towards the periphery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial advice for transforaminal lumbar interbody fusion (TLIF) was to place the intervertebral cage in the middle/posterior third of the disc space [25]. Posterolateral placement within the intervertebral space, where the endplate is thicker [8] and stronger [8,26], has been suggested following a biomechanical study assessing the risk of cage subsidence [14], whereas central placement has shown greater subsidence in a clinical study [15]. With regard to anterior placement, both a cadaveric [27] and a clinical study [28] involving TLIF found no difference in intervertebral lordosis when cages were placed in the anterior half of the disc space.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of normal sagittal alignment has been increasingly recognised in multi-segmental fusions for spinal deformity [1][2][3]. With increasing focus on patient-related outcomes, there is mounting evidence that optimum sagittal alignment in lumbar fusion is associated with improved outcomes across differing pathologies [1,[4][5][6][7][8][9], reduced post-surgical pain [1-3, 5-8, 10-13], reduced adjacent segment degeneration [4,5,7,[9][10][11][12][13][14], and reduced revision rates [1-5, 7, 9-11, 13, 15-18].…”
Section: Introductionmentioning
confidence: 99%